IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE (GCG) PRINCIPLES IN ZIS FUND MANAGEMENT REVIEWED FROM THE PERSPECTIVE OF PSAK 109 AT THE WIZ INSTITUTION OF BONE REGENCY - Nur Fajerin; Ismail Keri; Shadriyah (Islamic Economic and Business Journal, 2026)
Abstract This study aims to analyze the implementation of the principles of Good Corporate Governance (GCG) in the management of Zakat, Infaq, and Alms (ZIS) funds at the Wahdah Inspirasi Zakat Institute (WIZ) of Bone Regency, as well as test its suitability with PSAK 109 and identify the challenges faced. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the application of GCG principles in WIZ Bone Regency is reflected in the aspects of transparency, accountability, responsibility, independence, and fairness in the management of ZIS funds. From the perspective of PSAK 109, management and reporting practices have referred to applicable standards, especially in the presentation and distribution of funds. The challenges found include the limitations of amil competence as well as external coordination and public awareness in giving zakat. This study provides an evaluative overview of the practice of managing ZIS funds in local zakat institutions with the perspective of GCG and PSAK 109.   Abstrak Penelitian ini bertujuan untuk menganalisis implementasi prinsip Good Corporate Governance (GCG) dalam pengelolaan dana Zakat, Infak, dan Sedekah (ZIS) pada Lembaga Wahdah Inspirasi Zakat (WIZ) Kabupaten Bone, serta menguji kesesuaiannya dengan PSAK 109 dan mengidentifikasi tantangan yang dihadapi. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan prinsip GCG pada WIZ Kabupaten Bone tercermin dalam aspek transparansi, akuntabilitas, tanggung jawab, independensi, dan kewajaran dalam pengelolaan dana ZIS. Dari perspektif PSAK 109, praktik pengelolaan dan pelaporan telah mengacu pada standar yang berlaku, khususnya dalam penyajian dan penyaluran dana. Tantangan yang ditemukan meliputi keterbatasan kompetensi amil serta koordinasi eksternal dan kesadaran masyarakat dalam berzakat. Penelitian ini memberikan gambaran evaluatif mengenai praktik pengelolaan dana ZIS di lembaga zakat lokal dengan perspektif GCG dan PSAK 109.